2016
DOI: 10.1016/j.molcel.2016.11.020
|View full text |Cite
|
Sign up to set email alerts
|

Survival in Quiescence Requires the Euchromatic Deployment of Clr4/SUV39H by Argonaute-Associated Small RNAs

Abstract: Summary Quiescence (G0) is a ubiquitous stress response through which cells enter reversible dormancy, acquiring distinct properties including reduced metabolism, resistance to stress and long life. G0 entry involves dramatic changes to chromatin and transcription of cells, but the mechanisms coordinating these processes remain poorly understood. Using the fission yeast, here we track G0-associated chromatin and transcriptional changes temporally and show that as cells enter G0, their survival and global gene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 71 publications
(111 reference statements)
1
40
0
Order By: Relevance
“…Whereas RNAi machinery is required for establishing H3K9me at repetitive DNA elements and certain regulated genes 26,31 , RNAi-independent mechanisms involving MTREC and its associated factors assemble facultative heterochromatin at meiotic genes 14,17,25 . Our ChIP-chip and ChIP analyses showed that loss of the RNAi component Ago1 did not affect H3K9me peaks that are detected in cells grown at 18°C (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas RNAi machinery is required for establishing H3K9me at repetitive DNA elements and certain regulated genes 26,31 , RNAi-independent mechanisms involving MTREC and its associated factors assemble facultative heterochromatin at meiotic genes 14,17,25 . Our ChIP-chip and ChIP analyses showed that loss of the RNAi component Ago1 did not affect H3K9me peaks that are detected in cells grown at 18°C (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The RNA interference (RNAi) machinery targets facultative heterochromatin assembly at regulated genes 17,26,29,31 , in addition to constitutive heterochromatin assembly at centromeric repeats 27,32 . In another pathway, MTREC associated proteins recruit Clr4 to assemble facultative heterochromatin islands at meiotic genes 14,17,25,33 .…”
mentioning
confidence: 99%
“…We processed the data as mentioned in the corresponding download pages, before subjecting them to RAPID. We restricted our analysis to the sRNA-enriched genes available from their supplement [15] which can be accessed from https://bit.ly/2GSLcks. After pre-processing we subjected each GSM dataset to rapidStats, and compared them using rapidNorm.…”
Section: Schizosaccharomyces Pombementioning
confidence: 99%
“…The fission yeast, or Schizosaccharomyces pombe, is another widely studied unicellular eukaryotic model organism, where RNAi pathways are prevalent. We explored the time point datasets of WT, and three different knockdowns of S.pombe from the study by [15]. In this study, the authors investigated quiescence associated changes in small RNA transcriptomes and epigenetic modifications to identify the key players involved in quiescence.…”
Section: Analysis Of Schizosaccharomyces Pombe Knockdownsmentioning
confidence: 99%
See 1 more Smart Citation